Ride with the devil - Woodrell, Daniel 1953-; Danna, Mychael 1958-; Woodrell, Daniel 1953- (The Criterion collection, 2010)
In 1862, during the Kansas-Missouri border war, Jake and Jack Bull join the Confederate-sympathizing Bushwhackers after Jack's father is killed by marauding members of the abolitionist Jayhawkers. They are aided by unusual ally, Holt, who's fighting for the South despite being a former slave